Wastewater : From Waste to Resource - The Case of Santiago, Chile - World Bank Group (World Bank, Washington, DC, 2019)
A set of case studies was prepared as part of the World Bank's Water Global Practice initiative "Wastewater: from waste to resource" to document existing experiences in the water sector on the topic. The case studies highlight innovative financing and contractual arrangements, innovative regulations and legislation and innovative project designs that promote integrated planning, resource recovery and that enhance the financial and environmental sustainability of wastewater treatment plants. This case study documents Santiago, Chile.